Financial Cooperatives : Issues in Regulation, Supervision, and Institutional Strengthening - Cuevas, Carlos E. (World Bank, Washington, DC, 2018)
Financial Cooperatives (FCs) are important providers of financial services to poor and middle-income people, and significant drivers of financial inclusion. Aside from their strong presence and relevance in developed economies, especially Europe and North America, the significance of financial cooperatives in terms of financial inclusion in the developing world cannot be underestimated. Their pervasive presence in rural areas, and their potential to expand financial inclusion with multiple services to under-served segments make enabling the sustainable functioning of FCs a sensible policy objective. This paper reviews current knowledge about, and recent examples of FC development practice that generate lessons deemed valuable and useable in diverse contexts. The review provides background for an informed discussion around the following propositions: 1) Legal and regulatory frameworks for FCs adapted to the organizational nature and institutional structure of local FC entities; 2) Adequate legal and regulatory frameworks including appropriate safety nets following the development of the local FC market segment; and 3) Integrated approaches that combine legal and regulatory reforms with support to the institutional strengthening of the FC sector.